How the Potential Geotourism Packed to be Geoventure of Buleleng, North Bali - Widiastini Ni Made Ary; Agastya Ida Bagus Oka; Komang Krishna Darmawan (International Journal of Geotourism Science and Development, 2022)
Buleleng Regency, located in North Bali, has geological potential that can be developed into geotourism. There are dozens of waterfalls in Buleleng Regency, several caves that have their own uniqueness, and a beautiful hill stretching on the north side in the West Buleleng part. This paper aims to provide information about the potential of geotourism that can be packaged into a tour package in the form of a geoventure with the attractions visited are Sudaji Cave, Aling-aling Waterfall, Tembok Barak Waterfall, and Bukit Kursi Temple. The approach used is qualitative research with the geological diversity inventory method. Primary data was obtained through survey activities and direct observations in the field. From the research conducted, these four tourist attractions are geologically unique and can present an adventure exploring nature and is accompanied by knowledge of the landscape and culture of Buleleng. This geotourism activity targets those with a special interest in nature and culture, both domestic and foreign. The "geoventure" tour package starts from the East to the West, including the Sudaji Cave in Sudaji Village, then proceeds to Sambangan Village to enjoy and observe the Aling-aling Waterfall and the Barak Wall Waterfall, and then head to Bukit Kursi Temple. The travel time of the geoventure is estimated at more than seven hours so that packages can be made in the form of half-day tours.